The Influence Of Use Of The Discovery Learning Model On Learning Science Materials Changes In Form Of Substance On Student Learning Outcomes Class IV SDN Gugus Eleventh Bengkulu City - Yuliarti, Komang Ratna; Dalifa, Dalifa; Kurniawati , Ike (CV. Generasi Insan Rafflesia, 2025)
This research aims to determine the effect of using the discovery learning model in learning science and material regarding changes in the form of substances on the learning outcomes of class fourth students at SDN Gugus Eleventh, Bengkulu City. This research is quantitative research. The research method used was Quasy Experiment with the research design The Matching Only Pretest-Posttest Control Group Design. The population in this study were fourth grade students at SDN Gugus Eleventh Bengkulu City. The sample in this study consisted of 28 class fourth B students at SDN 5 Bengkulu City as the experimental class and 30 class fourth C students at SDN 41 Bengkulu City as the control class. The sampling technique uses Cluster Random Sampling, which means group randomization (study group). The instrument used in this research was a test sheet in the form of multiple choice with 10 questions. The test was taken twice, namely before and after learning took place in the experimental class and control class. From the results of the student's posttest t-test calculation, the Sig value (2 tailed) < 0,05 (0,000 < 0,05). This shows that there is a significant difference in the posttest results of the experimental class and the control class. Based on the results of the difference in posttest scores for the experimental class and the control class, it can be concluded that there is an influence of the use of the discovery learning model in science and science learning material on changes in the state of substances on the learning outcomes of class fourth students at Gugus Eleventh Elementary School, Bengkulu City.